Fault Location Effect on Short-Circuit Calculations of a TCVR Compensated Line in Algeria - Mohamed Zellagui; Heba Ahmed Hassan; Abdelaziz Chaghi (Institute of Advanced Engineering and Science, 2015)
This research work investigated the effect of fault location on short-circuit calculations for a high voltage transmission line equipped with a novel FACTS device, namely Thyristor Controlled Voltage Regulator (TCVR). This main function of this device was to control the voltage and active power of the line. The paper considered a study case for a 220 kV transmission line, in the Algerian transmission power network, which was subjected to a phase to earth fault in the presence of a fixed fault resistance. The paper presented theoretical analysis of the short-circuit calculations which was confirmed by the illustrated simulation results. Simulation results showed the impact of the fault location on the symmetrical current and voltage components of the line, and transmission line phase currents and voltages; before using TCVR and in the presence of TCVR for both cases of positive and negative TCVR controlled voltage.